A filtering polarization conversion electromagnetic surface for simultaneous RCS reduction and transmission - Huanhuan Yang; Tong Li; Jiawei Liao; Jing Zou; Tianhao Wu; Zexu Guo; Zhihao Li; Sijia Li (Results in Physics)
A novel bifunctional single-sheet electromagnetic surface is proposed in this paper. To alleviate the mutual coupling of the two functions, an equivalent series circuit for linear-to-linear polarization conversion and an equivalent parallel circuit for filtering property are cascaded. Thanks to the combination of different equivalent circuits and the displacement of the resonating parts of two functions, the proposed electromagnetic surface demonstrates filtering and polarization conversion properties in adjacent frequency bands. When the unit cell is periodically arranged to constitute a finite metasurface, more than 6 dB RCS reduction is obtained from 7.7 GHz to 22.8 GHz. The physical mechanism reveals that the low RCS property of the metasurface is in virtue of both scattering field cancellation and transmission. The simple structure, relatively small cell size and good performance of the metasurface suggest it may be a promising candidate as antenna radome. Moreover, the proposed integration method of different functions in one surface makes the design of multifunctional electromagnetic surface easier and faster.